Transcultural adaptation of the Healthcare Failure Mode and Effect Analysis (HFMEA) for use em Brazil: preview (Research, Society and Development, 2021)
Objective: to present the planning of the cross-cultural adaptation of the HealthCare Failure Mode and Effect Analysis (HFMEA) to the Brazilian culture. Method: this is a methodological study that will use the process of cross-cultural adaptation proposed by Beaton and collaborators, which includes six stages: initial translation, synthesis of translations, back-translations, expert committee, assessment of the pre-final version and evaluation and review of produced documents. To make up the committee of experts, professionals from different regions of the country will be selected to reach cultural differences and avoid language bias. The assessment of the pre-final version will be carried out with members of the Patient Safety Center of a hospital in southern Brazil, through the analysis of a case proposed by the researchers. The ethical precepts proposed by Resolution no. 466/2012 of the National Health Council will be respected. Final considerations: it is expected that the cross-cultural adaptation of HFMEA to Brazilian culture will encourage managers and institutions to carry out risk analysis in a systematic way. The method can assist in the identification of vulnerabilities in the process, directly affecting the care provided to patients and the establishment of safe practices.